“Atomisme” Dan “Hilomorfisme” Dalam Diskursus Pemikiran Islam - Akhmad Rofii Damyati (Arabic Literature Department STIBA DUBA PAMEKASAN, 2018)
Physics is the study of natural world. In the history of Islamic thought, there were two primary intellectual school in which nature was discussed: Atomism and Hylomorphism. Atomism is generally belong mutakallimin, or Islamic speculative theology, that in general approached issues in physics from an atomistic framework. While Hylomorphism is generally belong to Islamic philosophers that had its roots in the Greek intellectual tradition and more specifically in the philosophical thought of Aristotle. This writing is going to explain the atomistic theories found among the mutakallimin, that is called as “Atomism” shool of thought, followed by the Aristo-Avicennian natural philosophy, that is called as “Hylomorphism” school of thought.